2002
DOI: 10.1002/ijc.10440
|View full text |Cite
|
Sign up to set email alerts
|

Lovastatin potentiates antitumor activity of doxorubicin in murine melanoma via an apoptosis‐dependent mechanism

Abstract: Lovastatin, a drug successfully used in the clinic to prevent and to treat coronary heart disease, has recently been reported to decrease the incidence of melanoma in lovastatintreated patients. Lovastatin has also been proved to potentiate antitumor effects of both cisplatin and TNF-␣ in murine melanoma models. Recently, an augmented therapeutic effect of lovastatin and doxorubicin has been reported in 3 tumor models in mice. In our preliminary study lovastatin caused retardation of melanoma growth in mice tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
64
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(69 citation statements)
references
References 29 publications
(37 reference statements)
3
64
0
2
Order By: Relevance
“…A synergic effect with other antineoplastic agents, including doxorrubicine and selective cyclooxygenase inhibitors, has been observed. 5,6 While our small sample size limited the statistical power, we found a similar trend for improvement in melanoma risk. Further evaluation of the anticancer effects for statin drugs with a larger sample is warranted.…”
supporting
confidence: 53%
“…A synergic effect with other antineoplastic agents, including doxorrubicine and selective cyclooxygenase inhibitors, has been observed. 5,6 While our small sample size limited the statistical power, we found a similar trend for improvement in melanoma risk. Further evaluation of the anticancer effects for statin drugs with a larger sample is warranted.…”
supporting
confidence: 53%
“…At the present time, no association studies involving fluvastatin have been published yet; however, it has been previously shown that lovastatin enhanced the apoptosis induced by chemotherapeutic drugs, including 5-FU and cisplatin, in colon cancer cell lines (Agarwal et al, 1999). Furthermore, Holstein and Hohl (2001b) demonstrated synergism between paclitaxel and lovastatin on human cancer cell lines, whereas Feleszko et al (2002) showed an in vivo enhanced antitumour activity of doxorubicin in murine tumour models when associated with lovastatin.…”
Section: Discussionmentioning
confidence: 92%
“…26 Mevastatin, for example, inhibits bone resorption and induces osteoclast apoptosis in vitro by inhibition of protein prenylation. 27 Furthermore, statins have been shown to induce apoptosis in melanoma, 28 thyroid cancer, [29][30] colon carcinoma, 32,33 squamous cell carcinoma, 34 breast cancer, 35 acute myeloid leukemia, 36 malignant lymphoma, 37 and multiple myeloma cells 14,38 in vitro. In our experiments, statins have been used in much lower concentrations than in most in vitro studies published with complete reversal of CAM-DR, suggesting realistically achievable doses in humans.…”
Section: Discussionmentioning
confidence: 99%